Mixed Reality in Art Education - Back, Regina; Plecher, David A.; Wenrich, Rainer; Dorner, Birgit; Klinker, Gudrun (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
In this paper both receptive and productive Augmented Reality (AR)/Virtual Realty (VR)-Concepts to teach art are presented and discussed. Receptive means learning about art as an (immersed) spectator while productive means offering opportunities for own mixed reality artistic creations. The prototypes presented are pioneer research in terms of VR and AR, so called Mixed Reality (MR), informed art education. One of the core aims is to exemplify art educational applications by exploring usage of MR beyond traditional. The three MR based art educational concepts presented here invite users to experience art in heterogenous spatial contexts. MR is used here to highlight semantics of historically and art historically relevant spaces offering immersive as well as creative and participatory ways of learning. Three prototypes of MR informed art education are presented. First, a AR-based art history city guide is described with integration of teacher-based evaluation. Art is taught here in an interdisciplinary approach as situated learning experience visiting Munich's art historical sites and architecture. Teachers' attitudes towards AR/VR-based art history learning were conducted after trial of one of the applications. According to the educator's feedback, motivation, attention but also spatial imagination and perception are estimated to be fostered. Next, an AR-based installation of a missing painting by Franz Marc is presented conveying complex meanings of both architecture in art historical context as well as the art work itself. Finally, an immersive VR-art educational concept integrating two paintings of Caspar David Friedrich is described, offering sequential ways to inform about the painting's iconography. When it comes to implementing MR-concepts in day-to-day practice, media competence as well es technology acceptance or media cultural negotiations are vital aspects beyond the questions of it-technological equipment and infrastructure.